Low prioritization of latent tuberculosis infection—A systemic barrier to tuberculosis control: A qualitative study in Ontario, Canada. (7th November 2018) - Milinkovic, Deborah A.; Birch, Stephen; Scott, Fran; Newbold, K. Bruce; Hopkins, Jessica; Saffie, Muntasir; Essue, Beverley M.
Summary: Background: Eliminating tuberculosis (TB) in low‐incidence countries is an important global health priority, and Canada has committed to achieve this goal. The elimination of TB in low‐incidence countries requires effective management and treatment of latent tuberculosis infection (LTBI). This study aimed to understand and describe the system‐level barriers to LTBI treatment for immigrant populations in the Greater Toronto and Hamilton Area, Ontario, Canada. Methods: A qualitative study that used purposive sampling to recruit and interview health system advisors and planners (n = 10), providers (n = 13), and clients of LTBI health services (n = 9). Data were recorded, transcribed verbatim, and analyzed using content analysis. Results: Low prioritization of LTBI was an overarching theme that impacted four dimensions of LTBI care: management, service delivery, health literacy, and health care access. These factors explained, in part, inequities in the system that were linked to variations in health care quality and health care access. While some planners and providers at the local level were attempting to prioritize LTBI care, there was no clear pathway for information sharing. Conclusions: This multiperspective study identified barriers beyond the typical socioeconomic determinants and highlighted important upstream factors that hinder treatment initiation and adherence. Addressing these factors is critical if Canada is to meet the WHO's global call to eradicate TB in all low incidence settings.